ГДЗ до підручника «Алгебра» А.Г. Мерзляка. 7 клас

711. 1) а4 - b4 = (а2 - b2)(а2 + b2) = (а - b) • (а + b)(а2 + b2);

2) с4 - 81 = (с2 - 9)(с2 + 9) = (с - 3)(с + 3) • (с2 + 9).

712. 1) х4 - 16 = (х2 - 4)(х2 + 4) = (х - 2) • (х + 2)(х2 + 4).

2) y8 - 1 = (у4 - 1)(у4 + 1) = (у2 - 1)(y2 + 1) • (у4 + 1) = (у - 1)(у + 1)(у2 + 1)(у4 + 1).

713. 1) 4а3 - 4b3 = 4(а3 - b3) = 4(а - b) • (а2 + аb + b2).

2) 2m3 - 16 = 2(m3 - 8) = 2(m - 2)(m2 + 2m + 4).

3) 7 + 7b3 = 7(1 + b3) = 7(1 + b)(1 - b + b2).

4) -х4 + 27х = х(27 - х3) = х(3 - х)(9 + 3х + х2).

5) 2а4 - 250а = 2а(а3 - 125) = 2а(а - 5) • (а2 + 5а + 25).

6) 9а5 - 9а2 = 9а23 - 1) = 9а2(а - 1) • (а2 + а + 1).

714. 1) 3х3 + 3у3 = 3(х3 + у3) = 3(х + у) • (х2 - ху + у2).

2) 5m4 - 320mn3 = 5m(m3 - 64n3) = 5m(m – 4n)(m2 + 4mn + 16n2).

3) 6с5 - 6с8 = 6с5(1 - с3) = 6с5(1 - с)(1 + с + с2).

715. 1) а7 + аb6 = а(а6 + b6) = а(а2 + b2) • (а4 - а2b2 + b4).

2) x8 - у8 = (х4 - у4)(х4 + у4) = (х2 - у2)(х2 + y2)(х4 + y4) = (х - у)(х + у)(х2 + у2)(х4 + у4).

3) с6 - 1 = (с3 - 1)(с3 + 1) = (с - 1)(с2 + с + 1) • (с + 1)(с2 - с + 1).

716. 1) с6 + с9 = с6(1 + с3) = с6(1 + с)(1 - с + с2).

2) m9 - n9 = (m3 - n3)(m6 + m3n3 + n6) = (m - n)(m2 + mn + n2)(m6 + m3n3 + n6).

3) а8 - b4 = (а4 - b2)(а4 + b2) = (а2 - b)(а2 + b) • (а4 + b2).

717. 1) 3ab + 15b - 3а - 15 = 3b(а + 5) - 3(а + 5) = 3(b - 1)(а + 5).

2) 84 - 42y - 7xy + 14х = 42(2 - у) + 7х(2 - у) = (2 - у)(42 + 7х) = 7(2 - у)(6 + х).

3) abc + 6ас + 8аb + 48а = ас(b + 6) + 8а(b + 6) = (b + 6)(ас + 8а) = а(b + 6)(с + 8).

4) m3 - m2n + m2 - mn = m2(m - n) + m(m - n) = (m - n)(m2 + m) = m(m + 1)(m - n).

5) а3 + а2 - а - 1 = а2(а + 1) - (а + 1) = (а + 1) • (а2 - 1) = (а + 1)2(а - 1).

6) 2х3 - 2ху2 - 8х2 + 8у2 = 2х(х2 - у2) - 8(х2 - у2) = (х2 - у2)(2х - 8) = 2(х - у)(х + у) • (х - 4).

7) 5а2 - 5b2 - 15а3b + 15аb3 = 5(а2 - b2) - 15аb(а2 - b2) = (а2 - b2)(5 - 15аb) = 5(а - b) • (а + b)(1 - 3аb).

8) а2b2 - 1 - b2 + а2 = (а2b2 + а2) - (1 + b2) = а2(b2 + 1) - (1 + b2) = (b2 + 1)(а2 - 1) = (b2 + 1) • (а - 1)(а + 1).

718. 1) 15сх + 2су - сху - 30с = (15сх - 30с) + (2су - сху) = 15с(х - 2) + су(2 - х) = (х - 2)(15с - су) = с(х - 2)(15 - у).

2) 35а2 - 42аb + 10а2b - 12аb2 = 7а(5а - 6b) + 2аb(5а - 6b) = (5а - 6b)(7а + 2аb) = а(5а - 6b)(7 + 2b).

3) x3 + х2у + х2 + ху = х2(х + у) + х(х + у) = (х + у)(х2 + х) = х(х + у)(х + 1).

4) mn4 - n4 + mn3 - n3 = n4(m - 1) + n3(m - 1) = (m - 1)(n4 + n3) = n3(n + 1)(m - 1).

719. 1) (а2 + b2)2 - 4а2b2 = (а2 + b2 - 2аb) • (а2 + b2 + 2аb) = (а - b)2(а + b)2.

2) 81 - (х2 + 6х)2 = (9 - (х2 + 6х))(9 + (х2 + 6х)) = (9 - х2 - 6х)(9 + х2 + 6х) = (9 - х2 - 6х)(х + 3)2.

3) а2 + 2аb + b2 - с2 = (а + b)2 - с2 = (а + b - с) • (а + b + с).

4) с2 + 4с + 4 - k2 = (с + 2)2 - k2 = (с + 2 - k) • (с + 2 + k).

5) 9а2 + с2 + 6ас - 9 = (3а + с)2 - 32 = (3а + с - 3)(3а + с + 3).

6) а2 - b2 - 10b - 25 = а2 - (b + 5)2 = (а - b - 5)(а + b + 5).

7) 49 - у2 + х2 - 14х = (х2 - 14х + 49) - у2 = (х - 7)2 - у2 = (х - 7 - у)(х - 7 + у).

8) mn2 - m3 - 12m2 - 36m = m(n2 - (m2 + 12m + 36)) = m(n2 - (m + 6)2) = m(n - m - 6)(n + m + 6).

720. 1) (m2 - 2m)2 - 1 = (m2 – 2m - 1)(m2 - 2m + 1) = (m2 – 2m - 1)(m - 1)2.

2) 16 - (m2 + 4m)2 = (4 - m2 - 4m)(4 + m2 + 4m) = (4 - m2 - 4m)(2 + m)2.

3) х2 - 18ху + 81у2 - z2 = (х - 9у)2 - z2 = (х - 9у - z)(x - 9у + z).

4) 64х2 + 48ху + 9у2 - 144 = (8х + 3у)2 - 122 = (8х + 3у - 12)(8х + 3у + 12).

5) с2 - а2 + 22а - 121 = с2 -(а - 11)2 = (с - а + 11)(с + а - 11).

6) 100 - 25у2 - 60х2у - 36х4 = 102 - (5у + 6х2)2 = (16 - 5у - 6х2)(10 + 5у + 6х2).